Pelatihan Manajemen Koperasi Sekolah Untuk Mendukung Pendidikan Kewirausahaan Dan Ekonomi Mikro Di Kota Bandung - Andri Saputra; Rina Mulyani; Dedi Firmansyah; Siti Rahmah; Ahmad Fawzi; Lilis Handayani; Yoga Pratama (Bakti Masyarakat Pengabdian dan Pemberdayaan Masyarakat, 2025)
School cooperatives play a strategic role in developing entrepreneurial education and students' microeconomics skills, but their management still faces various managerial challenges. The aim of this community service activity is to improve the management competencies of school cooperatives to support entrepreneurship and microeconomics learning in Bandung City. The implementation method uses a participatory learning approach through workshops, practical training, mentoring, and monitoring and evaluation over three months. The results show a significant increase in aspects such as business planning (85%), financial management (78%), administration (82%), and students' entrepreneurial spirit (76%). The conclusion indicates that school cooperative management training effectively enhances the capacity of managers and has a positive impact on microeconomics learning and the development of students' entrepreneurial character within the school environment.